2015
DOI: 10.1021/ef502353m
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Properties and Accelerated Aging Test of Bio-oil Produced from in Situ Catalytic Pyrolysis in a Bench-Scale Fluidized-Bed Reactor

Abstract: In situ catalytic upgrading is a promising technique to improve the properties of bio-oil because the bio-oil produced from the conventional method has several negative attributes, such as low heating value and highly acidic nature, and is also unstable during storage. In this study, the catalytic effect of CaO, MgO, and ZSM-5 as in situ upgrading catalysts during biomass pyrolysis was studied in a fluidized-bed reactor. Southern pine sawdust was subjected to pyrolysis with inert bed material (quartz sand) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 37 publications
4
18
0
2
Order By: Relevance
“…1), which was modified from Mahadevan's study [27]. A screw feeder was driven by a motor to transfer biomass from a biomass feeder to fluidized bed reactor.…”
Section: Fast Pyrolysis Experimentsmentioning
confidence: 99%
“…1), which was modified from Mahadevan's study [27]. A screw feeder was driven by a motor to transfer biomass from a biomass feeder to fluidized bed reactor.…”
Section: Fast Pyrolysis Experimentsmentioning
confidence: 99%
“…cellulosic ethanol) or thermochemical (e.g. gasification, combustion, pyrolysis, and hydrothermal liquefaction) routes . Gasification is the process of partial combustion of biomass to produce a high calorific value gas, syngas, which is a combination of CO, H 2 , CH 4 , and CO 2 along with tar (condensable organic compounds) and other contaminants (NH 3 , H 2 S, HCN, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this current study was to develop a model that is able simulate the steady‐state output of the bench scale atmospheric fluidized bed gasifier that was experimentally studied in the earlier parts of this research. Experimental studies were conducted earlier in the course of this research to investigate the effects of temperature and CO 2 flow rate on biomass‐CO 2 gasification, and understand the chemistry of the process in a fluidized bed gasifier (reactor volume: 97 in; fluidized bed volume: 71 in) . This study identified the reactions dominating the process throughout the gasification temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Lai novērotu katalītisko efektu zinātniskos pētījumos parasti izmanto katalizatoru daudzumu, kas pēc masas ir līdzīgs [121,122,123] vai pat pārsniedz biomasas daudzumu [124].…”
Section: Katalītiskā Pirolīzeunclassified
“…Veses ar līdzautoriem[131] novēroja, ka CaO klātbūtnē notiek intensīva policiklisko aromātisko ogļūdeņražu veidošanās, līdzīgu tendenci termiski apstrādāta dolomīta klātbūtnē novēro arī Zhang ar līdzautoriem[227]. Autori secina, ka lignocelulozes pirolīzes , formaldehīds, acetaldehīds un acetons, tādēļ arī kviešu salmu pirolīzes procesā novēro ketonu un aldehīdu relatīvā iznākuma palielināšanos.Taču ketonu un aldehīdu veidošanās katalītiskajā kviešu salmu pirolīzē nav tik intensīva, cik ir organisko skābju daudzuma samazinājums CaO, Ca(OH)2 un 850 °C termiski apstrādāta dolomīta Kā jau iepriekš minēts, CaO, Ca(OH)2 un 850 °C termiski apstrādāta dolomīta (CaO•MgO) ietekmē novēro olefīnu relatīvā iznākuma palielināšanos, olefīnu veidošanās lignocelulozes procesā ir saistīta ar spirtu dehidratācijas reakcijām.Līdzīgu tendenci, ka kalciju saturošie katalizatori spēj samazināt anhidrocukuru un spirtu veidošanos, novēro arī citu autoru darbos[122,123,142], Patwardhan ar līdzautoriem[142] apgalvo, ka atšķirībā no ceolītiem, kas veicina furāna atvasinājumu veidošanos no anhidrocukuriem,…”
unclassified